A Takagi-Sugeno fuzzy-model-based finite-time H-infinity control for a hydraulic turbine governing system with time delay. (November 2021) - Ma, Teng; Wang, Bin; Zhang, Zhe; Ai, Bo
Highlights: A nonlinear time-delay hydraulic turbine governing system (HTGS) is established. A robust Takagi-Sugeno fuzzy finite-time H-infinity control method is proposed. A sufficient condition where the HTGS achieves finite-time stability is given. The gain matrices can be solved by the linear matrix inequality technique. The control method shows good robustness. Abstract: Hydraulic turbine governing systems (HTGSs) are complicated nonlinear systems with time delays, and stability control is an important factor for the safe operation of hydropower units. The control of an HTGS that focuses on Lyapunov asymptotic stability may have poor transient performance, and external disturbance will also make the control effect undesirable. Therefore, a robust Takagi-Sugeno (T-S) fuzzy finite-time H-infinity H ∞ (FFTH) control method for a nonlinear time-delay HTGS is proposed in this paper. First, a nonlinear time-delay HTGS model under a rigid water hammer is established, and its T-S fuzzy model is developed on the basis of fuzzy rules. Second, based on a selected Lyapunov candidate function, a sufficient condition where the fuzzy HTGS achieves finite-time stability and satisfies H ∞ performance along with the existence of a fuzzy controller is given in the form of linear matrix inequalities (LMIs). Finally, the numerical simulation results show that the designed control scheme resists random disturbances well and has better robustness compared to the conventional methods. It provides a new idea for the stability control of the HTGS and a reference for the practical engineering application.